Organized Corporate Planning Systems: An Empirical Study of Planning Practices and Experiences in American Big Business - Ringbakk, Kjell-Arne (Academy of Management Journal, 1968)
The article presents a dissertation abstract titled ?Organized Corporate Planning Systems: An Empirical Study of Planning Practices and Experiences in American Big Business,? by Kjell-Arne Ringbakk.